2019
DOI: 10.1039/c9ta07127j
|View full text |Cite
|
Sign up to set email alerts
|

Chelation-assisted formation of multi-yolk–shell Co4N@carbon nanoboxes for self-discharge-suppressed high-performance Li–SeS2 batteries

Abstract: A chelation competition induced polymerization strategy was exploited to prepare multi-yolk–shell Co4N@carbon nanoboxes, greatly enhancing the overall performance of Li–SeS2 batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 56 publications
3
21
0
Order By: Relevance
“…In addition, it was observed that SA has no considerable effect on the phase composition of SeS2, after 100 cycles at 0.2C, the XRD signals of the electrode have no obvious change (Fig. S15), which is consistent with previous reports [12,50] and this further confirmed that the CNC-0.05/SeS2 electrode has high electrochemical stability and the highly reversible conversion of SeS2. Moreover, after cycling, the surface structural features of the cycled cathode were further observed.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In addition, it was observed that SA has no considerable effect on the phase composition of SeS2, after 100 cycles at 0.2C, the XRD signals of the electrode have no obvious change (Fig. S15), which is consistent with previous reports [12,50] and this further confirmed that the CNC-0.05/SeS2 electrode has high electrochemical stability and the highly reversible conversion of SeS2. Moreover, after cycling, the surface structural features of the cycled cathode were further observed.…”
Section: Resultssupporting
confidence: 89%
“…It suggests that the cobalt doping of CNC-0.05/SeS2 can effectively inhibit the dissolution of high-order polysulfides/polyselenides into the electrolyte. Compared with CNC-0/SeS2, the onset evoked reduction peaks of CNC-0.05/SeS2 move towards higher voltage (2.06 V) and the oxidation peak moves toward a smaller voltage (2.28 V), and this promotes the redox potential difference of CNC-0.05/SeS2 is being significantly lower than CNC-0/SeS2, and this phenomenon suggests that the presence of CNC-0.05/SeS2 can effectively reduce the electrochemical polarization [12]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To meet the demand of high energy density Li–SeS 2 batteries, a high SeS 2 areal loading and a low electrolyte-to-selenium sulfide (E/SeS 2 ) ratio are commonly essential. However, most of recent studies on Li–SeS 2 batteries focused solely on the high capacity performance under a low SeS 2 areal loading (< 2.0 mg cm −2 ) and a high E/SeS 2 ratio (> 15 μL mg −1 ) [ 16 , 66 ]. As such, we further fabricated a series of high-areal-loading and low-E/SeS 2 -ratio cells with the CF@CNTs-NPP interlayers.…”
Section: Resultsmentioning
confidence: 99%